Psychometrics evaluation of Charcot‐Marie‐Tooth Neuropathy Score (CMTNSv2) second version, using Rasch analysis. Issue 3 (September 2014) - Sadjadi, Reza; Reilly, Mary M.; Shy, Michael E.; Pareyson, Davide; Laura, Matilde; Murphy, Sinead; Feely, Shawna M. E.; Grider, Tiffany; Bacon, Chelsea; Piscosquito, Giuseppe; Calabrese, Daniela; Burns, Ted M.
Abstract Charcot‐Marie‐Tooth Neuropathy Score second version (CMTNSv2) is a validated clinical outcome measure developed for use in clinical trials to monitor disease impairment and progression in affected CMT patients. Currently, all items of CMTNSv2 have identical contribution to the total score. We used Rasch analysis to further explore psychometric properties of CMTNSv2, and in particular, category response functioning, and their weight on the overall disease progression. Weighted category responses represent a more accurate estimate of actual values measuring disease severity and therefore could potentially be used in improving the current version. Copyright © 2014 John Wiley & Sons, Ltd.